Influence of Shiftwork on Greek Nursing Personnel - Anna Korompeli; Olav Muurlink; Chara Tzavara; Emmanouel Velonakis; Chrysoula Lemonidou; Panayota Sourtzi (Elsevier, 2014)
Background: The aim of this study was to investigate the burden experienced by nursing personnel working irregular shifts in Greece and to conduct the first test of a Greek version of the Standard Shiftwork Index (SSI). Methods: A cross-sectional survey was carried out. The SSI was completed by 365 nurses and nursing assistants working shifts, including nights. Results: Female nursing personnel and those suffering from a chronic disease were most affected by working rotating shifts as they had elevated scores on the majority of the SSI scales, such as sleep, chronic fatigue, digestive and cardiovascular problems, general health questionnaire, cognitive and somatic anxiety, shift time satisfaction, engagement and disengagement strategies, languidity, flexibility, and neurotisicm. Nurses with longer working experience and those with family responsibilities also scored higher on some of the SSI scales, such as the sleep, shift time satisfaction, social and domestic disruption, disengagement strategies, morningness, and languidity scales. Conclusion: Shiftwork affects female nurses, those with chronic disease, older age, and domestic responsibilities more severely. Therefore management should take these factors into account when designing work schedules to alleviate the burden caused by shiftwork.